PENGEMBANGAN TOOL WASTE TYPE WEIGHT ASSESSMENT MENGGUNAKAN MAKING TRIAL AND EVALUATION LABORATORY (DEMATEL) UNTUK MENDUKUNG KONSEP LEAN ASSESSMENT MATRIX - Fasa, S.T., M.T., Nadia; Handayani, Dwi; Angrayni, Septi Ayu (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2023)
One tool that can help eliminate waste is the lean assessment matrix (LAM). LAM is used to reduce waste by calculating the weight of the relationship between waste to obtain waste priorities. Waste prioritization considers assessment of severity, occurrence, interrelationships between waste and impact value. In the previous assessment matrix, calculating the weight of waste relationship values used the Waste Relationship Matrix (WRM) method, but the drawback of this tool was that the number of questions used was too many and the value conversion did not have a standard so it did not make it easy for respondents or human experts to measure the relationship between waste. So, in this research, Waste Assessment Waste Type Weight was developed by integrating the Decision Making Trial And Evaluation. Laboratory (DEMATEL) into LAM. Implementation of the Lean Assessment Matrix modification in the case study resulted in a priority rank of waste, namely Defect waste (W3, W2, W4) and Overprocessing waste (W16 and W15). The results of the LAM tool modifications carried out can help companies determine critical waste more easily and in line with company strategy.